1979
DOI: 10.1128/aac.16.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the penicillin-binding proteins of different strains of Neisseria gonorrhoeae

Abstract: This study was undertaken to determine if the categorization of Neisseria gonorrhoeae strains into disseminated gonococcal infection (DGI) and non-DGI types was also paralleled by some common characteristic in their penicillinbinding proteins (PBPs [MIC], c0.03 ,ug/ml), (iii) require arginine, hypoxanthine, and uracil for their growth (12), and (iv) can compete highly efficiently for iron (9). It was also demonstrated that serum resistance is associated with the possession of a principal outer membrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…An alteration in the cell envelope, such as that described by Sparling and co-workers (4,19), may contribute to resistance as well. The inability to explain the consistently greater susceptibility of those disseminated gonococcal infection strains examined in both this study and in the study of Nolan and Hildebrandt (15) (20,21). Gonococcal PBP 1 may, like E. coli PBP lb (23), be involved in cell wall expansion and in crosslinking peptidoglycan side chains.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…An alteration in the cell envelope, such as that described by Sparling and co-workers (4,19), may contribute to resistance as well. The inability to explain the consistently greater susceptibility of those disseminated gonococcal infection strains examined in both this study and in the study of Nolan and Hildebrandt (15) (20,21). Gonococcal PBP 1 may, like E. coli PBP lb (23), be involved in cell wall expansion and in crosslinking peptidoglycan side chains.…”
Section: Discussionmentioning
confidence: 69%
“…Some of these PBPs have been identified either with penicillin-sensitive enzymes involved in peptidoglycan synthesis (6,12,22,23) or, when enzyme specificity remains undefined, with a process such as cell septation or cylindrical growth (21,22). Neisseria gonorrhoeae, a gram-negative coccus, possesses PBPs as well (15,16). Little is known, however, of the functions of individual gonococcal PBPs.…”
mentioning
confidence: 99%
“…Similarly, preparations from the taxonomically related species Neisseria menigitidis and Neisseria sicca yielded PBP patterns similar to the pattern of gonococci. We did not observe strain-to-strain variation in the PBP pattern (16); differences in the details of the methodologies used (growth of cells, electrophoretic procedure) may account for this.…”
Section: Discussionmentioning
confidence: 85%
“…Previous reports in the literature (16,20) suggested that the PBPs of gonococci may vary from strain to strain. In contrast, we found that the PBP patterns of the strains that were routinely used were highly reproducible.…”
mentioning
confidence: 99%
“…The localization of this protein as well as its activity in the absence of antibiotics remains unknown. PBPs from other spherical cocci have not been localized, but the fact that Neisseria meningitidis or Neisseria gonorrhoeae have only four described PBPs (Nolan & Hildebrandt, 1979;Barbour, 1981;Stefanova et al, 2004), which include only one representative of HMW class A (PBP1) and one of HMW class B (PBP2) PBPs, may indicate that these species also have only one cell wall synthetic machinery.…”
Section: Pbp2bmentioning
confidence: 99%